Early nursery tests can lead to substantial genetic gain in Norway spruce field performance. Issue 8 (16th November 2020) - Högberg, Karl-Anders; Berlin, Mats; Helmersson, Andreas; Jansson, Gunnar
ABSTRACT: The effects of early selection in a nursery on field performance were studied in an experiment comprising 2665 cutting-propagated clones of Picea abies (L.) Karst, deriving from 151 half-sib families. The clones were selected from 13, 050 seedlings that were evaluated genetically using a randomized block design and measurements of height and growth rhythm in the nursery. The selected clones were assigned to six groups based on various criteria related to growth and phenology and to a comparison group of randomly selected clones. A group selected for height in the nursery gave an average gain in height after 6 years in the field of 9.1% compared with the randomly selected clones. Purely visual selection of plants with superior height, without considering the results of genetic evaluation, gave a gain of 3.8%. The gain in diameter after 12–14 years in the field was about two percentage units less but followed the same pattern. Other groups showed intermediate or less gain. Non-additive effects, expressed as clone-within-family effects, made substantial contributions to the total genetic gain. A test design that allows for genetic evaluation in the nursery appears to be a realistic option for achieving substantial gains in growth.